2019
DOI: 10.9775/kvfd.2018.20765
|View full text |Cite
|
Sign up to set email alerts
|

Bir Mantar Tarafından Üretilen Multi-enzimin Mısır-Soya Bazlı Rasyonla Beslenen Broyler Civcivlerinin Büyüme Performansı ve Karkas Parametrelerine Etkisi

Abstract: B: Effect of multi-enzyme produced by a single fungus on growth performance and some carcass parameters of broiler chicks fed on maize-soya based diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…Our results are in agreement with Mathlouthi et al [16] who reported that during the whole experimental period (1-40 d) FCR was decreased (P≤0.05) by β-glucanase supplementation. Our results are however, in inconsistent with those of Kalantar et al [17] who reported that supplementing wheat and barley diets with multienzymes increased total feed intake and decreased feed conversion ratio significantly (P<0.05) compared to non supplementation. Moreover, our results are inconsistent TASIRNAFAS, KARIMI, ASGARI JAFARABADI NOORBAKHSH, SEIDAVI Enzyme (IU) 0 0 0 10 IU Fib.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in agreement with Mathlouthi et al [16] who reported that during the whole experimental period (1-40 d) FCR was decreased (P≤0.05) by β-glucanase supplementation. Our results are however, in inconsistent with those of Kalantar et al [17] who reported that supplementing wheat and barley diets with multienzymes increased total feed intake and decreased feed conversion ratio significantly (P<0.05) compared to non supplementation. Moreover, our results are inconsistent TASIRNAFAS, KARIMI, ASGARI JAFARABADI NOORBAKHSH, SEIDAVI Enzyme (IU) 0 0 0 10 IU Fib.…”
Section: Discussioncontrasting
confidence: 99%
“…The cost of poultry feed ingredients represent about 60-70% of the total production cost, and hence, feed formulation is a critical approach in poultry industry. Feed utilization can be met with inclusion of enzymes, antimicrobials, probiotics, or prebiotic or natural products (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The endogenous enzymes of broiler chickens cannot adequately digest the dietary non-starch polysaccharides (NSP), and a high level of ingestion of these NSP by carbohydrases may exert anti-nutritional effects in broilers by increasing the digesta viscosity and decreasing the nutrient digestibility (Zeng et al, 2015). Exogenous enzymes are supplemented into corn-soya based poultry diets to reduce the effects of differing raw material quality, improve homogeneity and enhance nutrient digestibility (Yaqoob et al, 2022;Kutlu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%